Parasitoid of Dipterous collected in Brazil - Carlos Henrique Marchiori (Open Journal of Biological Sciences - Peertechz Publications, 2019)
Parasitoids are important regulators of insect populations and stand out as the main group of natural enemies in agricultural systems. They are present in various orders of insects and their adaptation to a parasitic behavior is seen most diversely and abundantly in the order Hymenoptera. The objective of this study was to increase the knowledge of the biology of a species of dipterous parasitoid in Brazil. The pupae were obtained using the flotation method. They were individually placed in gelatin capsules until the emergence of adult dipterous insects or their parasitoids. The experiments were conducted from January 1998 to February 2014 in rural and urban areas. The total percentage parasitism was 3.1%. Palaeosepsis spp. (Diptera: Sepsidae) were the hosts from which more individuals emerged with 52.3%. Spalangia drosophilae Ashmead (1885) (Hymenoptera: Pteromalidae) shows how biological characteristics to be a parasitoid pupal, ectoparasitoid, solitary and idiobiont.